Caffeic acid attenuates lipopolysaccharide-induced sickness behaviour and neuroinflammation in mice. (6th October 2016) - Basu Mallik, Sanchari; Mudgal, Jayesh; Nampoothiri, Madhavan; Hall, Susan; Dukie, Shailendra Anoopkumar -; Grant, Gary; Rao, C. Mallikarjuna; Arora, Devinder
Highlights: LPS induced sickness behaviour in mice, leading to reduced locomotor activity and increased immobility. CA treatment improved anti-oxidant defence and reversed the elevated TNF-α and IL-6. CA attenuated neuroinflammation mediated behavioural despair. Abstract: Accumulating data links inflammation, oxidative stress and immune system in the pathophysiology of major depressive disorders. Sickness behaviour is a set of behavioural changes that develop during infection, eventually leading to decrease in mobility and depressed behaviour. Lipopolysaccharide (LPS) induces a depression-like state in animals that mimics sickness behaviour. Caffeic acid, a naturally occurring polyphenol, possesses antioxidant and anti-inflammatory properties. The present study was designed to explore the potential of caffeic acid against LPS-induced sickness behaviour in mice. Caffeic acid (30 mg/kg) and imipramine (15 mg/kg) were administered orally one hour prior to LPS (1.5 mg/kg) challenge. Behavioural assessment was carried out between 1 and 2 h and blood samples were collected at 3 h post-LPS injection. Additionally, cytokines (brain and serum) and brain oxidative stress markers were estimated. LPS increased the systemic and brain cytokine levels, altered the anti-oxidant defence and produced key signs of sickness behaviour in animals. Caffeic acid treatment significantly reduced the LPS-induced changes, including reduced expression of inflammatory markers in serum and whole brain. Caffeic acid also exerted an anti-oxidant effect, which was evident from the decreased levels of oxidative stress markers in whole brain. Our data suggests that caffeic acid can prevent the neuroinflammation-induced acute and probably the long term neurodegenerative changes.